The Use of Dielectric Spectroscopy as a Tool for Predicting Meat Quality in Poultry - Samuel , D.; Trabelsi, S.; Karnuah, A.B.; Anthony, N.B.; Aggrey, S.E. (International Journal of Poultry Science, 2012)
Interest in Dielectric Spectroscopy (DS) has increased due to its potential use to predict meat quality in real time. We investigated the potential of using DS to predict meat quality characteristics such us pH, color, Water Holding Capacity (WHC), cook loss and drip loss in Pectoralis (P.) major muscle in broiler chicken. Dielectric properties were obtained utilizing a Hewlett-Packard 85070E open-ended coaxial-line probe and an N5230C PNA L-Network Analyzer through a flexible coaxial cable. Measurements were collected at 501 frequencies on a logarithmic scale from 200 MHZ to 50 GHz. The relationship between the quality measurements and the DP which included the dielectric constant, the dielectric loss factor and the dielectric loss tangent were determined using Pearson correlation. Low correlations were obtained between the dielectric constant and the dielectric loss factor and the quality parameters measured. However, the loss tangent showed a more promising relationship with the quality parameters at frequencies between 14 and 19 GHz. The results indicate the potential for utilizing DS as a tool for predicting of meat quality related to pH and color.